Dynamics of financial leverage across firm life cycle in Chinese firms: An empirical investigation using dynamic panel data model - Ajid ur Rehman; Man Wang; Haoyang Yu (China Finance and Economic Review, 2016)
Background: This study tries to investigate how firms adjust their leverage policy across the firm's life cycle. For this purpose the study uses an extensive set of data of 867 A listed Chinese non-financial firms over a nineteen years period (1996-2014). Methods: The study employs Arellano-Bover/Blundell-Bond dynamic panel data model to estimate adjustment rate of leverage and its determinants in three different life stages of Chinese firms. We find that adjustment rate of leverage varies for different life stages. Results: In accordance with trade off theory of capital structure this study reports a low-high-low pattern of leverage across growth, maturity and decline stage of firms' life respectively. For total leverage, dynamic panel data reports highest adjustment rate for growing firms, followed by mature firms and firms in declining stage of their life. Conclusions: Both short term and long term leverage report similar pattern of leverage's adjustment rate across the three stages of life cycle. The study provides useful insight in a unique market setting of Chinese financial markets.
Keywords: 330; Firm life cycle; Leverage; Chinese firms; Dynamic adjustment; GMM